The Post Graduate Studies-Reality and the Future Horizons (A Case Study in the Faculty of Agriculture University of Omar Al-Mouktar) - H. Elzobaidy , Dakhel; A. Ferkash , Mohammed; A. Mohammed, Mohammed (Al-Mukhtar Journal of Sciences, 2005)
This research aims to recognize on the real position of post graduate studies in the above mentioned university, through a case study in the faculty of agri. Data were collected randomly from (38) students and (35) staff-members. The results indicated that the staff-members had an educational and research experience ranging between (15-20) years, (66%) had the willing to continue their job as staff-members. The results also showed that (47%) from the researched students compla from the disability of some staff-members to convey knowledges, and (68%) complain the administrative procedures, (68%) complain the shortage of scientific references, the researchers put some recommendations for rising by the programes of post-graduate studies and activating the educational process.